„Promień ostry, który nas otwiera”. Światło w międzywojennej poezji Czesława Miłosza - Amroziewicz, Magdalena (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
In Czesław Miłosz’s poetry, light takes a special place. In my work, I have made an attempt to determine its role in the interwar poetry of the member of the Żagary literary group, in which light takes various shapes which are often contrary to one another. One can look at them in search of not only a variability of artistic forms, but also for testimonies of the era and declarations of contemporary poetic worldview of the author of Three Winters (Trzy zimy). The clash with various interpretations of the word ‘catastrophism’ shows that light in Miłosz’s poetry leads far beyond the course of history.